Distraction by Novel and Pitch-Deviant Sounds in Children - Wetzel, Nicole; Schröger, Erich; Widmann, Andreas (Frontiers in Psychology, 2016)
The control of attention is an important part of our executive functions and enables us to focus on relevant information and to ignore irrelevant information. The ability to shield against distraction by task-irrelevant sounds is suggested to mature during school age. The present study investigated the developmental time course of distraction in three groups of children aged 7 – 10 years. Two different types of distractor sounds that have been frequently used in auditory attention research – novel environmental and pitch-deviant sounds – were presented within an oddball paradigm while children performed a visual categorization task. Reaction time measurements revealed decreasing distractor-related impairment with age. Novel environmental sounds impaired performance in the categorization task more than pitch-deviant sounds. The youngest children showed a pronounced decline of novel-related distraction effects throughout the experimental session. Such a significant decline as a result of practice was not observed in the pitch-deviant condition and not in older children. We observed no correlation between cross-modal distraction effects and performance in standardized tests of concentration and visual distraction. Results of the cross-modal distraction paradigm indicate that separate mechanisms underlying the processing of novel environmental and pitch-deviant sounds develop with different time courses and that these mechanisms develop considerably within a few years in middle childhood.